EFEKTIVITAS PENDEKATAN DEEP LEARNING DENGAN MEDIA DIORAMA DIGITAL DALAM MENINGKATKAN HASIL BELAJAR IPAS PESERTA DIDIK KELAS IV SEKOLAH DASAR - Ilyas Nurul Habibi; Septina Rahmawati; Devy Aufia Abshor (STKIP Subang, 2026)
This study was motivated by the low level of understanding among fourth-grade elementary school students regarding the topic of climate and its changes in the IPAS subject. This condition is caused by the learning process that is still teacher-centered, resulting in students being less active in understanding concepts in depth. Learning that does not actively involve students can lead to low learning outcomes. Therefore, a more innovative learning approach is needed so that students can be actively involved and understand the material better. This study aims to determine the effectiveness of using the deep learning approach with digital diorama media on IPAS learning outcomes in the topic of climate and its changes for fourth-grade elementary school students. The research method used was a quantitative method with a quasi-experimental design using a nonequivalent control group design. The sampling technique used was purposive sampling. The research sample consisted of 44 students, including class IV A as the experimental class with 21 students and class IV B as the control class with 23 students. Data collection techniques included interviews, tests, and documentation, with research instruments in the form of pretest and posttest questions. Data analysis was conducted through the Shapiro–Wilk normality test, homogeneity test, independent sample t-test, paired sample t-test, and N-Gain test. The results showed that the significance value of the independent sample t-test was 0.000 < 0.05, indicating a difference in learning outcomes between the experimental and control classes. The average posttest score of the experimental class was 87.14, which was higher than the control class with an average score of 74.13. In addition, the average pretest score of the experimental class increased from 55 to 87.14 in the posttest.